2019
DOI: 10.1002/chem.201900513
|View full text |Cite
|
Sign up to set email alerts
|

Triplet Diradical‐Cation Salts Consisting of the Phenothiazine Radical Cation and a Nitronyl Nitroxide

Abstract: The spin–spin and magnetic properties of two (nitronyl nitroxide)‐(di‐p‐anisylamine‐phenothiazine) diradical cation salts, (DAA‐PTZ)+‐NN⋅MBr4− (M=Ga, Fe), have been investigated. These diradical‐cation species were prepared by the cross‐coupling of iodophenothiazine DAA‐PTZ‐I with NN‐AuPPh3 followed by oxidation with the thianthrenium radical cation (TA+⋅MBr4−). These salts were found to be highly stable under aerobic conditions. For the GaBr4 salt, large ferromagnetic intramolecular and small antiferromagneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 33 publications
(51 reference statements)
0
24
0
Order By: Relevance
“…A broad signal due to the Δ M s=±1 transition was observed and a spin‐forbidden signal (Δ M s=±2) appeared at a g =4 region. The observed EPR signal in the g =2 region was similar to those of the stable NN ‐substituted radical cation species [8b,d] . DFT‐calculations (UB3LYP/6‐31**) estimated ferromagnetic interaction with J / k B =+995 K between a NN and DOTT + spins (Figure 5b, Table S3) [14]…”
Section: Resultsmentioning
confidence: 92%
“…A broad signal due to the Δ M s=±1 transition was observed and a spin‐forbidden signal (Δ M s=±2) appeared at a g =4 region. The observed EPR signal in the g =2 region was similar to those of the stable NN ‐substituted radical cation species [8b,d] . DFT‐calculations (UB3LYP/6‐31**) estimated ferromagnetic interaction with J / k B =+995 K between a NN and DOTT + spins (Figure 5b, Table S3) [14]…”
Section: Resultsmentioning
confidence: 92%
“…[4a,b, 5] Thus, the mixeds table radicalw ith radical-cation molecules were provided for high-spin triplet ground state molecules. [1d, 6] As eries of nitronyl nitroxide (NN) substituted triarylamine (TAA-NN), [7] fused arylamine (FTAA-NN), [8] pyrazine (NNDPP), [9] thianthrene (TA-NN) [10] phenothiazine (PTZ-NN) [11] and pyrrole-based [2b] molecules and their radical-cationic forms were reported (FigureS1, Supporting Information( SI)), most of them afforded ground-state triplet diradicals upon one electron oxidation. In particular, 1-phenyl NN 4substituted-2,5-di(thiophen-2-yl)-1H-pyrrole derivatives (TPT-Ph-NN), [12] and NN-substituted conjugated oligomerso fd ithienyl-N-methylpyrrole with methoxys ubstituents at the inner b-position of thiophene rings type of molecules (DTP-P-NN), [13] were utilized for the synthesis of cationic high-spinm olecules.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to these studies, we previously designed, synthesized, and isolated nitronyl nitroxide radical (NN . )‐substituted radical cationic systems, based on diphenyldihydrophenazine (DPP .+ ‐NN . ), trioxytriphenylamine (TOT .+ ‐NN .…”
Section: Introductionmentioning
confidence: 99%
“…), and phenothiazine (PTZ .+ ‐NN . ), which were stable diradical systems in the triplet ground states with strong exchange interactions (2 J / k B > +300 K) (Scheme ). These experimental results also suggested that a strong donor π‐conjugated system substituted with NN .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation